The mechanical behaviour of cemented granular materials at high pressures - Marri, Amanullah (2010)
The mechanical behaviour of cemented granular materials has been an important topic in geotechnical engineering since decades. Historically, most research on ce-mented granular materials has been performed at relatively low confining pressures. Problems relating to cemented granular materials at high-pressure are still not fully understood. However, understanding of the behaviour of cemented granular materials at high-pressure is highly important in deep foundations, particularly for offshore piling, deep mine shafts, high earth dams, and oil-bearing strata. To address the problem, artificially cemented sand specimens with varying degrees of cement contents and initial relative densities were prepared in the laboratory to simulate the natural cementation characteristics. A high-pressure triaxial compression apparatus was utilized to investigate the effect of initial relative density, cement content, and confining pressure on the mechanical behaviour of artificially cemented sand. High-pressure tests including isotropic compression, drained and undrained triaxial shearing and microscopic studies of the materials were carried out on the artificially cemented sand specimens in the Nottingham Centre for Geomechanics laboratory at the University of Nottingham. Complexities with artificial specimen preparation and with high-pressure testing were identified and tackled. The experimental results indicate that there is significant effect of cement contents and confining pressures on the mechanical behaviour of cemented materials. Particularly, these effects were notified on isotropic compression, peaks strength, strength parameters, shear banding, particle crushing, yielding, and stress-dilatancy relationships. For example, reduction in compressibility, reduction in particle crushing and shift in normal compression line by the increase in cement content of the material during isotropic compression were significant. Progressive suppression in the dilation of cemented sand by the gradual increase in confining pressure, increase in the peak strength, developing of curved failure envelope, increase in the yield strength and formation of conjugate shear banding during progressive failure during triaxial compression were worth noticeable. This concludes that the significance of high-pressure and cement content cannot be ignored in the design considerations. However, more research needs to be carried out at further high pressures in order to see the convergence of failure envelopes and the initiation of bond breakage and particle crushing to give a reasonable design framework for foundations.